2023
DOI: 10.1021/acs.energyfuels.3c02298
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructured CoS2/MoS2 with a Rich Active Site for an Efficient Electrochemical Nitrate Reduction Reaction to Ammonia

Zixuan Tan,
Feng Du,
Mengqi Tong
et al.

Abstract: The electrochemical nitrate reduction reaction (NO 3− RR) has an important application value in realizing efficient synthesis of ammonia (NH 3 ) from NO 3 − , and obtaining a highperformance and low-cost electrocatalyst is the key. Nonetheless, a majority of the existing catalysts for the NO 3 − RR have the problem of an unsatisfactory NH 3 yield and insufficient stability. Herein, a heterostructured CoS 2 /MoS 2 electrocatalyst is designed and fabricated, and the structure−activity relationship is studied. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The electrochemical activity of the Ni foam electrode was significantly improved by the introduction of Co. The CoS 2 /MoS 2 heterostructure studied by Tan et al demonstrated that bimetallic interactions and electron transfer facilitated the reaction process. Excellent performance (97.07% FE and 95.45% NH 3 selectivity) was obtained for their electrocatalyst.…”
Section: Rational Selection and Design Of Electrocatalyst Materialsmentioning
confidence: 99%
“…The electrochemical activity of the Ni foam electrode was significantly improved by the introduction of Co. The CoS 2 /MoS 2 heterostructure studied by Tan et al demonstrated that bimetallic interactions and electron transfer facilitated the reaction process. Excellent performance (97.07% FE and 95.45% NH 3 selectivity) was obtained for their electrocatalyst.…”
Section: Rational Selection and Design Of Electrocatalyst Materialsmentioning
confidence: 99%
“…Ammonia is another decarbonized energy vector (like H 2 ), which can be produced by electrocatalytic conversion of N 2 . Tan et al proposed a heterostructured CoS 2 /MoS 2 catalyst for the synthesis of ammonia by the electrochemical nitrate reduction reaction. This heterostructure tailored reaction steps of the nitrate reduction and increased the NH 3 yield.…”
Section: Electrolysismentioning
confidence: 99%